A Comic Portrayal of the Troubles in Contemporary Drama - Rigonato, Alessandra Cristina (ABEI Journal, 2017)
This article aims to introduce a PhD research on the comic depiction of the Troubles (1968-1998) in Northern Irish drama. It will outline the issues of the diverse forms of the comic in the representation of the thirty-yearconflict. Amid the different tones for portraying the subject, the comic acquires a combination of satirical, ironic and black humoured tonalities in the work of Marie Jones, Martin Lynch, Tim Loane, Abbie Spallen and David Ireland.